Life cycle assessment of algae‐to‐biodiesel shallow pond production systems in the Mediterranean: influence of species, pond type, by(co)‐product valorisation and electricity mix. (1st March 2018) - Foteinis, Spyros; Antoniadis‐Gavriil, Antonis; Tsoutsos, Theocharis
Abstract: The environmental sustainability of microalgae‐to‐biodiesel production systems was examined at open (outdoor) and closed (indoor, using artificial light and temperature control) raceway ponds in a Mediterranean climate (southern Greece). Spirulina platensis and Nannochloropsis sp. species were considered, with the latter having a slightly better environmental performance. In terms of energy efficiency, large cumulative energy demand (CED) values were observed, while the energy return‐on‐investment (EROI) ratio was well below 3 in all cases, indicating that, with current technology, algae‐to‐biodiesel systems have not reached sustainability yet. The impact on land use was minimal, as nonarable land was used. Shallow‐pond cultivation systems are energy intensive, especially the closed ones, and therefore were found to be associated with high environmental footprints. In all cases, the main environmental hotspot was, by and large, the electricity consumption from the Greek fossil‐fuel depended energy mix (90%). Pellet, a process co‐product, largely reduced the total environmental footprint by up to ~47%, which highlights the importance of co‐product valorization. Closed systems exhibited significantly higher environmental footprints compared to open ones, due to the large energy inputs for artificial solar irradiation and for indoor temperature control. In all the cases examined, the microalgae‐to‐biodiesel production system's environmental footprint was higher than that of fossil diesel (i.e. petrodiesel), indicating that ample room exists to improve their environmental performance. A sensitivity analysis revealed that the introduction of renewable energy solely to cover for electricity needs substantially improves environmental sustainability and could render microalgae‐to‐biodiesel systems an environmentally friendlier solution than petrodiesel. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd